The Unintended Ecological and Social Impacts of Food Safety Regulations in California's Central Coast Region. (19th November 2015) - Karp, Daniel S.; Baur, Patrick; Atwill, Edward R.; De Master, Kathryn; Gennet, Sasha; Iles, Alastair; Nelson, Joanna L.; Sciligo, Amber R.; Kremen, Claire
Abstract: In 2006, a multistate Escherichia coli O157:H7 outbreak linked to spinach grown in California's Central Coast region caused public concerns, catalyzing far-reaching reforms in vegetable production. Industry and government pressured growers to adopt costly new measures to improve food safety, many of which targeted wildlife as a disease vector. In response, many growers fenced fields, lined field edges with wildlife traps and poison, and removed remaining adjacent habitat. Although the efficacy of these and other practices for mitigating pathogen risk have not been thoroughly evaluated, their widespread adoption has substantial consequences for rural livelihoods, biodiversity, and ecological processes. Today, as federal regulators are poised to set mandatory standards for on-farm food safety throughout the United States, major gaps persist in understanding the relationships between farming systems and food safety. Addressing food-safety knowledge gaps and developing effective farming practices are crucial for co-managing agriculture for food production, conservation, and human health.